Wykorzystanie wybranych modeli analizy dyskryminacyjnej w ocenie sytuacji finansowej przedsiębiorstw produkujących pasze - Czerwińska-Kayzer, Dorota; Florek, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The main target of the article was to present selected Polish models of early warning and to assess their adaptation to indicate a deterioration in the financial situation of enterprises producing animal feed. The presented research shows that the use of different models of early warning doesn’t give base to unambiguous evaluation of the company’s financial situation.